Iron‐Functionalized Silica Nanoparticles as a Highly Efficient Adsorbent and Catalyst for Toluene Oxidation in the Gas Phase. Issue 4 (4th January 2013) - Popova, Margarita; Ristić, Alenka; Lazar, Karoly; Maučec, Darja; Vassileva, Mihaela; Novak Tušar, Nataša
Abstract Catalytic oxidation is one of the most important industrially applicable processes for the decomposition of volatile organic compounds (VOCs) in polluted air. The advanced VOC removal process is composed of an adsorption unit and a catalytic incinerator. Many efforts have been made to design a combined adsorption–catalytic unit with optimal activity and selectivity. We demonstrate that iron‐functionalized silica nanoparticles with interparticle mesoporosity (FeKIL‐2) act as highly efficient adsorbents and catalysts with optimal Fe/Si molar ratios of 0.01 in toluene oxidation as model VOCs in the gas phase. By using UV/Vis, FTIR, and Mössbauer spectroscopic techniques, we prove that the enhanced activity of the catalyst is attributed to iron incorporated into the silica matrix, which depends on the iron content. The iron content with Fe/Si≤0.01 leads to the formation of stable Fe3+ ions in the silica matrix, which ensures easier oxygen release from the catalyst (Fe3+/Fe2+ redox cycles). The increase in the iron content with Fe/Si>0.01 leads to the formation of oligonuclear iron complexes. The material thus introduces a promising, environmentally friendly, cost‐effective, and highly efficient catalyst with combined adsorption and catalytic properties for the removal of low‐concentration VOC from polluted air.